2018
DOI: 10.1016/j.bbmt.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

A Conditioning Regimen with Plerixafor Is Safe and Improves the Outcome of TCRαβ+ and CD19+ Cell-Depleted Stem Cell Transplantation in Patients with Wiskott-Aldrich Syndrome

Abstract: Our initial experience with hematopoietic stem cell transplantation (HSCT) from a matched unrelated donor (MUD; n = 12) or a haploidentical related donor (n = 6) with T cell receptor (TCR)αβ/CD19 graft depletion in patients with Wiskott-Aldrich syndrome (WAS) (n = 18) showed a dramatic decrease in the incidence of graft-versus-host disease (GVHD) and transplantation-related mortality, with an increased overall survival (OS) of 88.9%. Unfortunately, the treatment was associated with mixed myeloid donor chimeris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 25 publications
(38 reference statements)
1
30
0
4
Order By: Relevance
“…Similar to the WAS patients in this study by Balashov et al [2], Konopleva et al [15] recently found that leukemic patients treated with G-CSF and plerixafor during pretransplant myeloablative conditioning for alloHCT also had increased donor myeloid chimerism and lower rates of GVHD compared with historical controls not receiving mobilizing agents. Because cohorts of conditioned patients were not treated with only 1 of the mobilizing agents in either of these studies, it is unclear whether both G-CSF and plerixafor are required to enhance donor engraftment and reduce subtransplant complications after alloHCT.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Similar to the WAS patients in this study by Balashov et al [2], Konopleva et al [15] recently found that leukemic patients treated with G-CSF and plerixafor during pretransplant myeloablative conditioning for alloHCT also had increased donor myeloid chimerism and lower rates of GVHD compared with historical controls not receiving mobilizing agents. Because cohorts of conditioned patients were not treated with only 1 of the mobilizing agents in either of these studies, it is unclear whether both G-CSF and plerixafor are required to enhance donor engraftment and reduce subtransplant complications after alloHCT.…”
supporting
confidence: 80%
“…Therefore, increasing donor engraftment so as to minimize mixed chimerism could increase the efficacy of alloHCT for WAS. In this study, Balashov et al [2] report increased donor engraftment and event-free survival following addition of G-CSF and plerixafor to the conditioning regimen of WAS patients undergoing alloHCT with TCR αβ/CD19-depleted haploidentical or matched unrelated grafts. Patients underwent a reduced toxicity myeloablative conditioning regimen consisting of treosulfan (days -5 to -3), fludarabine (days -6 to -3), and melphalan (day -2) with the addition of G-CSF (days -8 to -4) and plerixafor (days -6 to -4).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In the absence of a matched-donor, decision to transplant needs to be balanced. Transplantation from an alternative donor is more challenging even though most recent results show increasingly successful survival, allowing to consider transplant early in the disease course (43)(44)(45)(46). At the end, the final decision about transplant will depend on a conjunction of factors such as immunological parameters, the severity of past and current clinical manifestations, i.e., severity of infections, autoimmunity, need of immunosuppressive treatment to control the manifestations related to immune dysregulation and donor compatibility.…”
Section: Defects Of T-cell Productionmentioning
confidence: 99%